2018
DOI: 10.1002/jcp.27283
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel biomarkers for hepatocellular carcinoma using transcriptome analysis

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of death from cancer in the world. To comprehensively investigate the utility of microRNAs (miRNAs) and protein-encoding transcripts (messenger RNAs [mRNAs]) in HCC as potential biomarkers for early detection and diagnosis, we exhaustively mined genomic data from three available omics datasets (GEO, Oncomine, and TCGA), analyzed the overlaps among gene expression studies from 920 hepatocellular carcinoma samples and 508 healthy (or adjacent normal) live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 71 publications
0
27
0
Order By: Relevance
“…The unprecedented proliferation of recent large-scale and multiomics databases of cancers provides numerous new insights into genomic and epigenomic dysregulation in cancer discovery (Rappoport and Shamir, 2018). Publicly available databases like TCGA, METABRIC, or GEO, which are common in the cancer research community, help better understand tumor heterogeneity, detect biomarker genes, and define hidden molecular mechanisms in multi-omics research (Xia Q. et al, 2019). Moreover, lines of previous evidence indicate notable relationships between CNA and mRNA, such as there is a high association of CNA with the development and progression of cancers by regulating gene expression level (Huang et al, 2017;Samulin Erdem et al, 2017;Zhou et al, 2017;Gut et al, 2018), as well as the similar regulatory associations between MET and mRNA (Herman and Baylin, 2003;Shen and Laird, 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The unprecedented proliferation of recent large-scale and multiomics databases of cancers provides numerous new insights into genomic and epigenomic dysregulation in cancer discovery (Rappoport and Shamir, 2018). Publicly available databases like TCGA, METABRIC, or GEO, which are common in the cancer research community, help better understand tumor heterogeneity, detect biomarker genes, and define hidden molecular mechanisms in multi-omics research (Xia Q. et al, 2019). Moreover, lines of previous evidence indicate notable relationships between CNA and mRNA, such as there is a high association of CNA with the development and progression of cancers by regulating gene expression level (Huang et al, 2017;Samulin Erdem et al, 2017;Zhou et al, 2017;Gut et al, 2018), as well as the similar regulatory associations between MET and mRNA (Herman and Baylin, 2003;Shen and Laird, 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…24,25 Therefore, multi-omics studies can help determine tumor heterogeneity and screen therapeutic targets and tumor biomarkers, which have greater advantages. 26 The study screens and identifies 9-gene signature associated with COAD prognosis by analyzing multi-omics data, including transcriptome data, copying number variation data and mutation data. The 9-gene signature established by screening has strong robustness and stable prediction performance in both internal verification set and external verification set.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, high-throughput sequencing provides a better understanding of HCC-related lncRNAs. A large number of dysregulated lncRNAs have been identified, and they are associated with a variety of biological processes in HCC, such as cell proliferation, apoptosis, migration, invasion, and angiogenesis 19 – 21 . Emerging researches have revealed that SNHG family plays important roles in tumorigenesis and the immune escape of cancer via sponging miRNA 22 – 24 .…”
Section: Discussionmentioning
confidence: 99%